Eficiența basmului în educația școlară. Perspectiva actuală a cadrelor didactice din România și Republica Moldova [Articol] - Ungureanu, Maria (CEP USM, 2024)
In the article we present the results of research on the formative effects of the fairy tale. We will describe the current perspective of teachers from Romania and the Republic Moldova on the efficiency of fairy tale in cognitive, affective and volitional development of young schoolchildren. The data were collected within a pedagogical experiment carried out between February and May 2023, in schools on both banks of the Prut River. The verified hypothesis affirms the manifestation by teachers from Romania and the Republic Moldova of a reluctant attitude towards capitalizing the fairy tale in instructive-educational activities. The results of the research confirm the hypothesis and provide the necessary data to describe the conception of teachers about the effectiveness of fairy tales in education.
THE EFFECTIVENESS OF THE FAIRY TALE IN SCHOOL EDUCATION. THE CURRENT PERSPECTIVE OF TEACHERS IN ROMANIA AND THE REPUBLIC OF MOLDOVA
Keywords: basm; dezvoltare cognitivă; dezvoltare afectivă; educație